Determining South African National Parks' contribution to sustainable development goals in host communities: A case study of Kruger National Park - Mabibibi, Mashudu Andra (Vaal University of Technology, 2023)
The study examines and evaluates the Kruger National Park’s role in assisting its host communities to meet their Sustainable Development Goals agenda. The study is triggered by the fact that the tourism industry is criticised for its unsustainable practices and exploitative proclivities. The existence of knowledge gaps on how the KNP operations and activities fullfil and lead to the realisation of SDGs, therefore, warrants research so as to generate information and strategies that are beneficial not only to the KNP only, but also to the communities that are located in its proximity. The study conducted between March and October 2021, used a case study reseach design in a mixed method approach to answer the research questions. The emperical work comprised of in-depth interviews (=30) with key informants identified by KNP gatekeppers; surveys (=70) with community members; a secondary literatire review; and observations of community projects done by host communities - artefacts sold within and outside the park, infrastructure developments in communities and agricultural practices in host communities. Thematic analysis was used to catergorise the data according to the corresponding SDG categories. The study found that despite hurdles such as climate change, diminished funding, and COVID-19, among other such factors, the Kruger National Park aided communities in meeting at least 15 of the 17 SDGs goals. The various projects of the KNP address all the SDGs except for SDG7 on affordable and clean energy and SDG 14 on life below water where no identified project could be directly linked to those SDGs. It was also found that some of the KNP’s flagship projects were ensuring economic emancipation, delivering quality education, and alleviating poverty and inequality, all of which interlink with conservation and environmental protection. The projects have also fostered some sense of ownership by local communities, a move which has helped improve relations between the park and host communities. The study recommends continuous monitoring of the role that protected areas can play in addressing the 17 SDGs. Continuous monitoring will allow for necessary interventions to be made at the policy and practical levels.
M. Tech. (Department of Travel and Tourism Service Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Sustainable Development Goals; National parks; Host community; Kruger National Park; South Africa; Sustainable tourism; Dissertations, Academic -- South Africa.; Sustainable development.; Sustainable tourism.; Community development -- Management.; Tourism -- South Africa.